Parasite-infected-cell-agglutination and indirect immunofluorescence assays for detection of human serum antibodies bound to antigens on Plasmodium falciparum-infected erythrocytes. - Marsh, K; Sherwood, J; Howard, R (1986)
Two methods are described for detecting the binding of serum antibodies from adults in an endemic malarious area (The Gambia) to surface antigens on Plasmodium falciparum-infected erythrocytes. An antibody-mediated parasite-infected-cell-agglutination assay (without secondary antibody) and an indirect immunofluorescence assay employing an anti-Fc secondary reagent were used to detect bound antibody. The surface of erythrocytes containing mature parasites bound antibody, but the surface of uninfected cells or cells containing early parasite stages did not react. Serum from 'non-immune' Europeans did not agglutinate infected erythrocytes, however, in the immunofluorescence test with anti-Ig and anti-F(ab')2 secondary reagents we could detect the binding of IgG antibody from 'non-immune' European serum to a small proportion of infected cells. In contrast to the results with freshly collected isolates, antibodies from sera of Gambian adults did not bind to the surface of infected cells from five different culture-adapted isolates of P. falciparum. These assays are suitable for studies on the antigenic diversity of erythrocyte antigens in natural infections and specific antibody responses to these antigens in infected patients.